Pengaruh Strategi Pembelajaran Online dan Gaya Belajar terhadap Hasil Belajar Aplikasi Konsep - Pratama, Angga (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This study aims to determine the differences in the learning outcomes of the application of concepts to students who learn to use online strategies with face-to-face learning strategies, as well as to test whether there is a difference in the average learning outcomes of the application of concepts to students who have different learning styles and to test whether there is an interaction between learning strategies and learning outcomes. learning styles on the learning outcomes of student concept applications. This study used a quasi-experimental research design. 2x2 factorial design The variables of this study are the independent variables are online learning strategies and face-to-face learning, the control variables are learning styles and the dependent variable is the learning outcomes of concept application. This research instrument is a question of pretest and posttest which was developed in accordance with the research objectives of the lectures listed in the RPS. The hypothesis testing of this research uses 2-way Analysis of Variance (ANOVA) to test the hypothesis, in the form of the Univariate Test of Between-Subject Effects. The results of this study indicate (1) there are significant differences, including learning outcomes of student concept applications using online learning strategies with face-to-face learning strategies. The use of online learning strategies is significantly superior to face-to-face learning strategies., (2) there is a significant difference in the acquisition of concept application learning outcomes between students who have an active learning style and a reflective learning style, significantly students who have an active learning style are more superior in learning outcomes of concept applications compared to students who have reflective learning styles. (3) there is an interaction between online learning, learning strategies and learning styles on concept application learning outcomes. the influence between the interaction, the independent variable and the moderator variable on the dependent variable, both for the learning outcomes of the application of the concept.